Organizational behavior emerging knowledge, global reality - McShane, Steven L.; Von Glinow, Mary Ann Young 1949- (McGraw-Hill Education, 2021)
"Organizational Behavior explains how emotions are the foundation of employee motivation, attitudes, and decisions; how social networks generate power and shape communication patterns; how self-concept influences individual behavior, team cohesion and leadership; and how adopting a global mindset has become an important employee characteristic in this increasingly interconnected world"-- Provided by publisher.